CAOS D2D: Uma Solução para Offloading de Métodos entre Dispositivos Móveis - Santos, Gabriel B. dos; Rego, Paulo A. L.; Gomes , Francisco A. A.; Trinta, Fernando (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
In spite of the increasing processing power of smart handheld devices, their capacity is always a few steps behind their contemporary desktop counterparts. Besides, mobile devices have limited power supplies, which leads software designers to keep energy consumption in mind. An alternative to help overcome this issue is using the offloading (or cyber foraging) technique, which allows a mobile device to offload an expensive task to another device, for the sake of performance or energy saving. This second device may be a remote server hosted in a public cloud, or in the same Wi-Fi network as the first mobile device (i.e., a cloudlet). This paper presents CAOS D2D: a framework which allows a mobile device to offload tasks to another mobile device, as well as acting as an offloading server too. We briefly describe the development process of our implementation, starting from another offloading solution developed by our research group. We also describe CAOS D2D architecture and provide a small usage example with code snippets. And finally, we define some future works to guide the evolution path of our solution.